Pengaruh Joyful Learning Berbasis Gamifikasi terhadap Kemampuan Berpikir Kritis Siswa Kelas V pada Pembelajaran Bahasa Indonesia - Annisa Oktavia; Nurul Hidayah; Yudesta Erfayliana (Mataram University, 2026)
Critical thinking is a key twenty-first-century competency that remains insufficiently developed in primary education, particularly in Indonesian language learning. This study aimed to examine the effect of gamification-based joyful learning on the critical thinking skills of fifth-grade students. A quasi-experimental method with a non-equivalent control group design was employed. The study involved 37 fifth-grade students at SDN 1 Purwodadi, Central Lampung, consisting of an experimental group (18 students) and a control group (19 students). The experimental group received gamification-based joyful learning, whereas the control group was taught using a scientific approach. Data were collected through validated and reliable essay-based Pre-test and Post-test instruments and analyzed using an independent samples t-test. The results showed that the experimental group achieved a higher mean Post-test score (82.12) than the control group (72.86). Hypothesis testing revealed a significance value of p < 0.001 (p < 0.05), indicating a statistically significant effect of gamification-based joyful learning on students’ critical thinking skills. These findings demonstrate that integrating gamification elements, including points, badges, leaderboards, and tiered challenges, within an enjoyable learning environment can effectively enhance students’ critical thinking, confidence in expressing opinions, and ability to analyze information in Indonesian language learning.